Coherent Photoproduction of e+e- Pairs in Ge in Conditions of Strong Collimation of Secondary Particles - Andreyashkin M. Yu.; Zabaev V. N. Viktor Nikolaevich; Kalinin B. N.; Kunashenko Yu. P.; Pivovarov Yu. L. Yuriy Leonidovich (1999, 1999)
В фонде НТБ ТПУ отсутствует